Ledakan Informasi dan Kesehatan Mental: Peran Kecerdasan Emosional di Era Digita - Rahmah, Fathiyah Rahmah; Sutami, Nasywa Az-Zahra Sutami; Amanda, Mahfuzhah Dwi Amanda; Asbari, Masduki Asbari (Journal of Information Systems and Management (JISMA), 2025)
The information explosion in today's digital era has had a significant impact on individuals'mental health, particularly in the form of increased stress and anxiety. One relevant concept inaddressing this challenge is emotional intelligence, introduced by Daniel Goleman, which serves as anadaptive mechanism for managing the psychological effects of the ever-growing stream of information.This study aims to examine the role of emotional intelligence as an adaptive solution in coping with theinformation explosion that can affect individual well-being. Using a descriptive qualitative approach,this research analyzes statements made by Ryu Hasan in Gita Wirjawan’s podcast titled “Intelligenceand Happiness from a Neuroscience Perspective”, published on the YouTube platform. The discussionreveals that emotional intelligence can help individuals build emotional resilience, filter informationwisely, and respond to digital pressures more constructively. This study emphasizes the importance ofstrengthening emotional capacity as an essential resource to endure in the age of information overload.Keywords: Digital era, emotional intelligence, information overload, mental health, psychologicalimpact